Effects Of Phototherapy On Serum Calcium Level In Neonates With Hyperbilirubinemia - Javaid, Qura-tul-Ain; Aziz, Salma; Noor-ul-Ain; Abid, Uzma; Afzal, Ayesha; Javaid, Umer (Journal of Rawalpindi Medical College, 2023)
Objective: To study the frequency of hypocalcemia in neonates receiving phototherapy with indirect hyperbilirubinemia Materials and Methods: Descriptive case series study was conducted from September 5, 2018, to March 5, 2019, in the NICU of the Paediatric Department Benazir Bhutto Hospital, Rawalpindi. Approval was sought from the hospital’s ethical committee. Neonates fulfilling inclusion criteria were enrolled in the study after obtaining informed consent from the parents. Before giving phototherapy, serum calcium levels were checked. Phototherapy was given for 48 hours. Serum calcium levels were reassessed after 48 hours of phototherapy. Data was entered on a structured proforma and statistical analysis of data was performed. Results: Out of 150 patients enrolled in the study 83(55.33%) were male and 67(44.67%) were female. The mean age of patients was 52.52 hours with minimum and maximum ages of 26 hours and 80 hours. The mean Indirect serum bilirubin level was 15.59 ± 2.36. A total of 50(33.33%) cases had hypocalcemia after 48 hours of phototherapy, all of these neonates had normal calcium levels before phototherapy. When hypocalcaemia was stratified for gestational age, birth weight and serum bilirubin levels at baseline, there was no significant difference in the frequency of hypocalcaemia concerning these effect modifiers. Conclusion: It is concluded that the frequency of hypocalcemia is higher in neonates with indirect hyperbilirubinemia after receiving phototherapy. One needs to be vigilant in dealing with neonates in this context, while serial measurements of calcium levels and monitoring for complications of hypocalcaemia should be included in every institution’s policy